Advantages and Limitations of Current Imaging Techniques for Characterizing Liposome Morphology - Robson, Annie-Louise; Dastoor, Paul C.; Flynn, Jamie; Palmer, William; Martin, Antony; Smith, Doug W.; Woldu, Ameha; Hua, Susan (Frontiers in Pharmacology, 2018)
There are currently a number of imaging techniques available for evaluating the morphology of liposomes and other nanoparticles, with each having its own advantages and disadvantages that should be considered when interpreting data. Controlling and validating the morphology of nanoparticles is of key importance for the effective clinical translation of liposomal formulations. There are a number of physical characteristics of liposomes that determine their in vivo behaviour, including size, surface characteristics, lamellarity and homogeneity. Despite the great importance of the morphology of nanoparticles, it is generally not well characterized and difficult to control. Appropriate imaging techniques provide important details regarding the morphological characteristics of nanoparticles, and should be used in conjunction with other methods to assess physicochemical parameters. In this review, we will discuss the advantages and limitations of available imaging techniques used to evaluate liposomal formulations.